INNV-21. EFFECTIVE REGIMEN OF HIGH-DOSE METHOTREXATE PLUS TEMOZOLOMIDE FOR PRIMARY CENTRAL NERVOUS SYSTEM LYMPHOMA: A SINGLE-CENTER RETROSPECTIVE STUDY - Zhang, Jun-ping (Neuro Oncol, 2020)
OBJECTIVE: To evaluate the efficacy and safety of high-dose methotrexate combined with temozolomide in the treatment of newly diagnosed primary central nervous system lymphoma. METHODS: A retrospective study was performed to analyze the clinical data of patients with primary central nervous system lymphoma treated with high-dose methotrexate plus temozolomide in the Department of Neuro-oncology, Capital Medical University, Sanbo Brain Hospital from May 2010 to December 2018. RESULTS: A total of 41 patients were identified. Median age was 57 years (range, 27–76 years). The maximal extent of surgery was total resection in 6, partial resection in 8, and biopsy in 27 patients. Of the 35 patients with evaluable lesions, 32 achieved complete response (CR) and 3 achieved partial response. CR rate was 91.4%. The median follow-up time was 36.5 months (range, 4.9–115.4 months). After treatment, the median progression-free survival (PFS) was 45.1 months. PFS rate at 1, 2, 5 years were 85.4%, 70.1% and 43.8%, respectively. The OS rate at 1, 2, 5 years were 92.7%, 82.4% and 66.5%, respectively. The median PFS of patients younger than 65 years was better than that of patients ≥65 years (98.8 months vs 27.9 months, p=0.039). There was no association between efficacy and extent of resection (p=0.836). After disease progression, 6 of the 21 patients received radiotherapy. There was no statistical difference in OS between the patients with or without radiotherapy (36.9 months vs 28.4 months). The main severe adverse events were myelosuppression (36.6%) and elevated transaminase (34.1%). Three patients were discontinued due to drug-related toxicities. CONCLUSIONS: High-dose methotrexate combined with temozolomide is effective in the treatment of primary central nervous system lymphoma, with a low incidence of severe adverse reactions. This efficacy may be better than the historical control of methotrexate alone or methotrexate plus rituximab.